Revision. The problems of pollution in the metallurgical industry. - Habashi, Fathi (2012)
The mineral processing and metal production have increased significantly in recent years. As a result, the amounts of waste materials and pollutants are also increasing. In many cases, technology has changed to address the problem. The processes have been modified to either reduce emissions, or replaced by others that are less polluting, albeit at a higher cost. Are briefly presented, examples of ferrous and non-ferrous industries.